Polyradical PROXYL/TEMPO‐Derived Amides: Synthesis, Physicochemical Studies, DFT Calculations, and Antimicrobial Activity1. Issue 11 (17th November 2017) - Poprac, Patrik; Poliak, Peter; Kavala, Miroslav; Barbieriková, Zuzana; Zalibera, Michal; Fronc, Marek; Švorc, Ľubomír; Vihonská, Zuzana; Olejníková, Petra; Lušpai, Karol; Lukeš, Vladimír; Brezová, Vlasta; et al.
Abstract: A series of polynitroxide amides possessing 2, 2, 5, 5‐tetramethyl‐1‐pyrrolidinyloxy (PROXYL) and/or 2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxy (TEMPO) units connected through various bridges were synthesized and their properties were analyzed. EPR spectroscopy provided detailed insight into their paramagnetic character and related properties. A thorough examination of the EPR spectra of dinitroxides in organic solvents provided valuable information on the intramolecular motions, thermodynamics, and spin‐exchange mechanisms. Analysis of low‐temperature X‐ and Q‐band EPR spectra of the dissolved dinitroxides provided spin–spin distances that were comparable with the theoretical values obtained by DFT. Cyclic voltammetry investigations revealed (quasi)reversible electrochemical behavior for PROXYL‐derived biradicals, whereas significant loss of the reversibility was found for TEMPO‐containing bi‐ and polyradicals. The inhibitory activities of the nitroxides against model bacteria, yeasts, and filamentous fungi were assessed. Abstract : Flexibility and communication : A series of di‐ and polynitroxide amides possessing 2, 2, 5, 5‐tetramethyl‐1‐pyrrolidinyloxy (PROXYL) and/or 2, 2, 6, 6‐tetramethyl‐1‐piperidinyloxy (TEMPO) units were synthesized and their properties were analyzed through multiple experimental techniques, including X‐ and Q‐band EPR spectroscopy, X‐ray diffraction, cyclic voltammetry, and DFT calculations (see figure). An assessment of their inhibitory activities against selected bacteria, yeasts, and filamentous fungi revealed the highest activity for TEMPO‐derived tetraradicals.